Evaluating the Processing of Hides within a Green Industry Framework: Implications for Sustainable Livestock By-product Utilization - Amalia, Dian Nur; Fauziah, Qori Nur; Rahmawati, Atiqa; Ajie, Baskoro; Robbika, Fadzkurisma (Unpad Press, 2026)
The leather industry is an important sector in utilizing livestock by-products, contributing to economic value addition and resource efficiency in animal production. However, conventional tanning processes remain a major environmental concern due to the excessive use of hazardous chemicals such as chromium and salt. This review aims to analyze cleaner tanning innovations that support sustainable livestock hide production and explore their potential integration into circular livestock systems. The study was conducted through an extensive literature review of national and international sources focusing on enzymatic tanning, vegetable tanning, and the application of circular bio-economy concepts. The findings indicate that the use of enzymes, plant extracts, and biopolymers can reduce the dependency on toxic chemicals, decrease wastewater load, and improve water and energy efficiency. Integrating these innovations within circular livestock systems enhances the utilization of livestock by-products, including waste conversion into biogas, organic fertilizer, and bio-based tanning materials. Therefore, the development of cleaner tanning technology based on livestock hides is a strategic approach toward establishing a green leather industry that supports sustainable livestock production.